Interpreting psychological warfare: understanding religious extremism from a discourse analysis approach / Ahmad Sauffiyan Abu Hasan - Abu Hasan, Ahmad Sauffiyan (Institute of Graduate Studies, UiTM, 2015)
This thesis investigates the meaning of “psychology” in psychological warfare by explaining the factors that permit the existence of religious extremist behavior. Such attention are been given because the problem is relatively understudied in Malaysia and that has resulted in the inability to develop an ideal psychological warfare model to deal with the problem. Since 2001, Malaysia has been labeled as a breeding ground for religious extremist leaders. The recurring number of religious extremist cases magnifies our limited understanding on the psychological context of the problem and if left unattained, can prolong the situation. To propose a theoretical solution to the problem, three research objectives were formulated and they are: (1) how existential psychology can be used to explain religious extremism, (2) how behavioral psychology can be used to explain religious extremism and (3) how psychoanalytical psychology can be used to explain religious extremism. Conclusively, discourse analysis on 37 psychological constructs extracted from three psychological paradigms of Frankl, Pavlov & Skinner, and Freud have enabled this study to theorize a multi-factor stand to look at the problem, hence confirming the root cause of it…